Assessing the Heat Tolerance of Meiosis in Spanish Landraces of Tetraploid Wheat Triticum turgidum - Tomás Naranjo; Nieves Cuñado; Juan Luis Santos (Plants, 2022)
Heat stress alters the number and distribution of meiotic crossovers in wild and cultivated plant species. Hence, global warming may have a negative impact on meiosis, fertility, and crop productions. Assessment of germplasm collections to identify heat-tolerant genotypes is a priority for future crop improvement. Durum wheat, Triticum turgidum, is an important cultivated cereal worldwide and given the genetic diversity of the durum wheat Spanish landraces core collection, we decided to analyse the heat stress effect on chiasma formation in a sample of 16 landraces of T. turgidum ssp. turgidum and T. turgidum ssp. durum, from localities with variable climate conditions. Plants of each landrace were grown at 18–22 °C and at 30 °C during the premeiotic temperature-sensitive stage. The number of chiasmata was not affected by heat stress in three genotypes, but decreased by 0.3–2 chiasmata in ten genotypes and more than two chiasmata in the remaining three ones. Both thermotolerant and temperature-sensitive genotypes were found in the two subspecies, and in some of the agroecological zones studied, which supports that genotypes conferring a heat tolerant meiotic phenotype are not dependent on subspecies or geographical origin. Implications of heat adaptive genotypes in future research and breeding are discussed.